Pelatihan Perawatan Tanaman Sayuran pada Teknik Vertikultur untuk Keberlangsungan Kemandirian Pangan Masyarakat Perkotaan di Masa Pandemi - Fani Ardiani; Githa Noviana; Yohana Theresia Maria Astuti (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This training was conducted at the Sang Timur Boys' Dormitory in the city of Yogyakarta. This activity aims to increase the knowledge, insight, and skills of residents and hostel administrators in vertical care, and also assist government programs in adapting new habits by reducing outdoor activities and increasing food security in urban areas. The methods used at the time of implementation included socialization, mentoring in planting vegetable seeds (water spinach and mustard greens), training in the manufacture of liquid fertilizer, and provision of lettuce, spinach, and water spinach seeds for the next planting period. The result of the activity is that the vertical installations owned by the hostel can be managed and utilized properly. In addition, the residents and administrators of the hostel gain knowledge, insight, and skills in plant care in verticulture techniques and the manufacture of liquid fertilizer that can be used on their plants.